Millennials' Investment Interest in Quick Response Code Indonesian Standard - Ulla Ulfatin Khoiriyah; Anna Widiastuti (Penerbit Goodwood, 2026)
Purpose: This study aims to examine the influence of financial literacy, trust level, and service quality on millennials’ investment interest in the QRIS platform in Jepara Regency, Indonesia. Methodology/approach: This research employs a quantitative approach using survey data collected from 160 millennial respondents selected through random sampling method. Data were obtained using Likert-scale questionnaires that met the validity and reliability criteria. The collected data were analyzed using multiple linear regression with SmartPLS software to evaluate the relationships between variables. Results/findings: The findings indicate that financial literacy and trust have a positive and significant effect on millennials’ investment interest in the QRIS platform. Financial literacy emerged as the most dominant factor influencing investment interest, followed by trust level. In contrast, service quality has a positive but insignificant effect. These results suggest that cognitive understanding of financial management and confidence in platform security play a more critical role than technical service attributes in shaping digital investment behaviors. Conclusions: Millennials’ investment interest in the QRIS platform is primarily driven by financial literacy and trust rather than service quality. This confirms that psychological and cognitive factors are the central determinants of digital investment behavior among millennials. Limitations: This study is limited to millennial respondents in Jepara Regency and focuses only on three independent variables, which may restrict the generalizability of the findings to other regions. Contributions: This study provides empirical evidence of investment behavior within the QRIS platform, highlighting its unique role beyond digital payments. The findings offer practical insights for policymakers and financial service providers to enhance millennials’ investment participation through improved financial literacy and trust-building.